2015
DOI: 10.3109/17435390.2015.1107146
|View full text |Cite
|
Sign up to set email alerts
|

Thioridazine in PLGA nanoparticles reduces toxicity and improves rifampicin therapy against mycobacterial infection in zebrafish

Abstract: Encapsulating antibiotics such as rifampicin in biodegradable nanoparticles provides several advantages compared to free drug administration, including reduced dosing due to localized targeting and sustained release. Consequently, these characteristics reduce systemic drug toxicity. However, new nanoformulations need to be tested in complex biological systems to fully characterize their potential for improved drug therapy. Tuberculosis, caused by infection with the bacterium Mycobacterium tuberculosis, require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…Thus, Tukulula et al [36] reported no cytotoxic effect of PLGA NPs and curdlan-conjugated PLGA NPs in THP1 macrophages over a 72 h period (dose range from 0.13 to200 µg/mL). In primary murine macrophages, thioridazine and rifampicin loaded-PLGA NPs and unloaded PLGA NPs did not significantly reduce cell viability throughout a 9 days treatment [37]. Also, PLGA NPs were not toxic to Caco2 cells after 24 h exposition, as long as the concentration was lower than 500 μg/mL [38].…”
Section: Discussionmentioning
confidence: 86%
“…Thus, Tukulula et al [36] reported no cytotoxic effect of PLGA NPs and curdlan-conjugated PLGA NPs in THP1 macrophages over a 72 h period (dose range from 0.13 to200 µg/mL). In primary murine macrophages, thioridazine and rifampicin loaded-PLGA NPs and unloaded PLGA NPs did not significantly reduce cell viability throughout a 9 days treatment [37]. Also, PLGA NPs were not toxic to Caco2 cells after 24 h exposition, as long as the concentration was lower than 500 μg/mL [38].…”
Section: Discussionmentioning
confidence: 86%
“…Considering that the intravenous administration of small molecular agents lacks the ability to precisely achieve tumor tissues, the application of chemotherapeutic agents, anti‐CSC agents, and PD‐1/PD‐L1 inhibitors together is badly in need of a vector for their delivery toward tumor cells, otherwise there will not be sufficient accumulation in tumors if administrated in low dosage, or might cause systemic side effects in high dosage . This could be achieved by nano drug delivery systems (NDDS), which own the capacity of encapsulating different drugs at the same time and targeting tumor via the enhanced permeability and retention (EPR) effect .…”
mentioning
confidence: 99%
“…Promising examples of the future use of thioridazine in new short term therapeutic regimens against any form of antibiotic resistance of Mtb come from the recent studies that demonstrated the possibility of effectively using nanoparticles containing thioridazine and rifampicin for rapid tuberculosis treatment in vitro and in a zebrafish model [101,102]. The use of TZ as a therapeutic adjuvant for anti-TB therapy is currently being expanded in Argentina and India.…”
Section: Discussionmentioning
confidence: 99%